Transcallosally mediated inhibition of interneurons within human primary motor cortex - Schnitzler, A; Kessler, K R; Benecke, R (Experimental brain research, 1996)
The objective of this study was to investigate interhemispheric transcallosal connections between primary motor cortices noninvasively in awake human subjects. For this purpose, focal transcranial magnetic stimulation was performed on eight healthy, right-handed subjects and one patient with congenital collosal agenesis. Using two magnetic stimulators, we investigated the effect of a conditioning magnetic stimulus applied to the motor cortex of one hemisphere on the duration of the silent period (SP) evoked in the first dorsal interosseus (FDI) muscle by a magnetic test stimulus given over the opposite motor cortex. It is well established that SP reflects activation of inhibitory interneurons within primary motor cortex. In all normal subjects, a conditioning stimulus to one hemisphere produced a significant shortening of SP evoked by the test stimulus when the conditioning-test-interval was 10-20 ms. The effect was also observed when an electrical test stimulus was used. The conditioning coil had to be placed over the hand motor area to obtain the maximal effect. The threshold for eliciting this decrease of SP duration was higher than the threshold for eliciting an early excitatory muscle response in the contralateral FDI. Increasing the intensity of the conditioning stimulus led to linear reduction of SP duration. In the patient with callosal agenesis, no such decreasing effect on SP duration was observed. These results suggest that inhibitory interneurons within primary hand motor cortex receive transcallosal inhibitory input from the opposite motor cortex. We propose that modulation of motor cortical interneurons via transcallosal pathways may provide a gain control for the motor cortical output system and subserve interhemispheric coordination in complex, nonsymmetrical bimanual movements.